Inter-observer agreement in interpreting chest X-rays on children with acute lower respiratory tract infections and concurrent wheezing - Bada, Carlos; Carreazo, Nilton Yhuri; Chalco, Juan Pablo; Huicho, Luis (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Many children with acute lower respiratory tract infections (ALRI) present to the emergency ward with concurrent wheezing. A chest x-ray is often requested to rule out pneumonia. We assessed inter-observer agreement in interpreting x-rays on such children. DESIGNS AND SETTING: Prospective consecutive case study at Instituto de Salud del Niño, Lima, Peru. METHODS: Chest x-rays were obtained from eligible children younger than two years old with ALRI and concurrent wheezing who were seen in the emergency ward of a nationwide pediatric referral hospital. The x-rays were read independently by three different pediatric residents who were aware only that the children had a respiratory infection. All the children had received inhaled beta-adrenergic agonists before undergoing chest x-rays. Lobar and complicated pneumonia cases were excluded from the study. RESULTS: Two hundred x-rays were read. The overall kappa index was 0.2. The highest individual kappa values for specific x-ray findings ranged from 0.26 to 0.34 for rib horizontalization and from 0.14 to 0.31 for alveolar infiltrate. Inter-observer variation was intermediate for alveolar infiltrate (kappa 0.14 to 0.21) and for air bronchogram (kappa 0.13 to 0.23). Reinforcement of the bronchovascular network (kappa 0.10 to 0.16) and air trapping (kappa 0.05 to 0.20) had the lowest agreement. CONCLUSIONS: There was poor inter-observer agreement for chest x-ray interpretation on children with ALRI and concurrent wheezing seen at the emergency ward. This may preclude reliable diagnosing of pneumonia in settings where residents make management decisions regarding sick children. The effects of training on inter-observer variation need further studies.